Antioxidant effects of rhodomyrtus tomentosa (Kemunting) extract on the development of experimental atherosclerotic-induced New Zealand white rabbit / Muhamad Fahrin Maskam - Maskam, Muhamad Fahrin (2011)
The in vitro study was conducted to determine the antioxidant activity of R. tomentosa in water, methanol, chloroform and petroleum ether extract. In DPPH assay, methanol extract had the highest antioxidant capacity with IC50 of 107μg/ml. Antioxidant activity of R. tomentosa measured using FRAP assay also showed that methanol extract had the highest antioxidant capacity 0.162nm at concentration of 500μg/ml. While in Metal Chelating assay again showed methanol extract had the most chelating ability of all extracts with 36% at concentration of 100μg/ml. The chemical compounds found in R. tomentosa were quercetin, gallic acid and tannic acid from HPLC analyses; malic acid, caffeic acid, dihydrocaffeic acid, quinic acid, brevifolin carboxylic acid, octadecenoic acid and galloyl glucose from GCMS analyses. Total phenolic content (TPC) of the extracts estimated as gallic acid equivalent was highest in water extract at 66.515mg/g dry mass. Total flavonoid content (TFC) estimation was highest in water extract measured at 1.828mg/ml. Toxicity of the extracts was assessed in vitro by Artemia salina lethality. The result showed, water extract of R. tomentosa was the most non-toxic with LC50 at 616.083μg/ml. Group of rabbits treated with tomentosa extract had significantly lower (p<0.05) in LDL and total cholesterol (TC) against cholesterol group. Meanwhile high density lipoprotein (HDL) did show significant increase (p<0.05) compared to cholesterol group. The study also showed a significant reduction of lipid peroxidation index indicated by low TBARs-MDA level (p<0.05) in tomentosa group compared to cholesterol group. Histopathology analysis of aorta presented with thick foam cell formation in cholesterol group, however there were less foam cell formation in tomentosa and simvastatin group. Kidney and liver showed less infiltration of inflammatory cell. In conclusion, the supplementation of 50mg/kg/day of R. tomentosa extract was able to prevent and reduce the progression of atherosclerotic plaque development induced by dietary cholesterol of 1%. The reduced progression was due to the chemical compounds rich in antioxidant and other bioactive compounds.